(untitled) (Archaeologia Adriatica, 2012)
Remains of a Neolithic settlement were found in excavations in 2012 at the periphery of the city of Benkovac, at the Barice position. Discovery of dwelling objects was accompanied by rich remains of material culture. Analyzed and presented finds correspond closely to well-known cultural expression of the typical Danilo culture. Standard assemblage of pottery and artifacts made of stone and bone was enriched with objects appearing rarely in the eastern Adriatic Neolithic.